2015
DOI: 10.1186/s12913-014-0672-4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing implementation challenges during guideline development – a case study of Swedish national guidelines for methods of preventing disease

Abstract: BackgroundMany of the world’s life threatening diseases (e.g. cancer, heart disease, stroke) could be prevented by eliminating life-style habits such as tobacco use, unhealthy diet, physical inactivity and excessive alcohol use. Incorporating evidence-based research on methods to change unhealthy lifestyle habits in clinical practice would be equally valuable. However gaps between guideline development and implementation are well documented, with implications for health care quality, safety and effectiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…A longitudinal, comparative case study approach was applied. Case study 1 focused on the development and implementation of national guidelines for methods of preventing disease that took place between 2007 and 2014 [ 20 ]. Case study 2 explored the development and implementation of a national policy aiming to improve the quality and coordination of care for the most ill older people, between 2009 and 2014 [ 21 ] (for descriptions of the cases, see Additional file 1 and for description of the healthcare system and actors, see Additional file 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…A longitudinal, comparative case study approach was applied. Case study 1 focused on the development and implementation of national guidelines for methods of preventing disease that took place between 2007 and 2014 [ 20 ]. Case study 2 explored the development and implementation of a national policy aiming to improve the quality and coordination of care for the most ill older people, between 2009 and 2014 [ 21 ] (for descriptions of the cases, see Additional file 1 and for description of the healthcare system and actors, see Additional file 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, broad agreement on purpose can contribute to raised motivation and organizational readiness among target users [ 26 , 27 ]. In this study, we found that health authorities decided to develop national guidelines to meet the challenges of growing antimicrobial resistance and variations in antibiotic use between hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…According to Grol and Wensing ( 2013a ), the optimal point in time at which to adjust guidelines to suit an organization is during implementation. Constructing and marketing guidelines as flexible enough to suit difference between municipalities would likely facilitate their implementation (Richter-Sundberg et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Grol and Wensing's ( 2013b ) model, it has been concluded that these comprise the actual innovation; the practitioners; the clients; culture in the workplace; the economic, administrative, and organizational context; and the choice of strategy for the implementation and dissemination of the innovation. Accordingly, a Swedish study showed that guideline developers could benefit from an initial assessment of how the actual topic, the target context, and the stakeholders affected the implementation (Richter-Sundberg, Kardakis, Weinehall, Garvare, & Nystrom, 2015 ). In addition, a Canadian study found several barriers to the implementation of best practice guidelines into a public health setting, which were consistent with earlier research, such as time constraints, working in multidisciplinary teams, and system-level changes in leadership (Athwal et al, 2014 ).…”
mentioning
confidence: 99%